PENTAHELIX MODEL IN DEVELOPING ANCIENT VILLAGE IN INDONESIA - Prasiwi Citra Resmi; Bobur Sobirov Baxtishodovich (International Journal of Social Science, 2024)
Wisata Kampung Purba Dayu, Gondangrejo, and Karanganyar villages are designated tourist villages based on Regent Decree No. 556/378 of 2020. The existence of the Dayu Antiquities Museum, covering an area of 10,500 m2, is a supporting capacity for a prehistoric life science research center. This Museum stores various fossils that were once found in Dayu Village, which are traces of the journey of ancient humans. This Museum is fascinating to be used as a tourist destination for people of various ages. A separate reason why Dayu Village has become its own ancient village tourism village is that the village has a natural beauty that is still maintained on its natural side and treasures traditional culture. It is hoped that development program activities can reduce community poverty. This study analyzes the development strategy of Dayu Ancient Village. Data can be descriptively qualitative and analyzed using SWOT analysis techniques. The results of this study show that the S-O (strength-opportunities) strategy applied aims to use the strengths possessed by utilizing existing opportunities. The S-T (Strengths-Threats) strategy aims to utilize the strengths to minimize existing threats. Existing threats. W-O (Weakness-Opportunities) strategy aims to minimize weaknesses owned by utilizing existing opportunities. The W-T (weakness-threat) strategy aims to minimize weaknesses to avoid threats. The results showed that in making a tourism village development strategy through the application of the Pentahelix model, it is hoped that it can be implemented and can help the community in uniting the goals of developing a well-impacted and conceptualized tourism village, especially in Dayu Gondangrejo Ancient Village, Karangayar. Using the pentahelix model through the A4 stage (attractions, accessibility, amenities, and ancillary) can be a short stage in terms of the development structure of a tourist village, of course, through close collaboration between related pentahelix. Through collaborative communication from academia, business, community, government, and media, the strategies found here are the existence of 4 Identification and seen from internal and external factors or extreme weakness, opportunity, and treatment, where the SO, WO Energy, ST Energy, and WT energy strategies produce 5 strategies each that can be applied in Dayu Ancient Village.